2020
DOI: 10.31415/bjns.v3i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Melaleuca spp. essential oil and its medical applicability. A Brief Review

Abstract: Medicinal plants have long been used as an alternative in the treatment of diseases, whether using extracts, essential oils and / or bioactive components. Thus, the use of medicinal plants, with popularly known effects for the treatment of infections, has gained prominence, in research related to extracts and essential oils of medicinal plants, in an attempt to discover and future application of new molecules with antimicrobial and / or effect coadjuvant molecules to antimicrobials on the market. Studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(7 reference statements)
0
7
0
1
Order By: Relevance
“…Recently, in vivo trials conducted on melaleuca gel were reported to have an inhibitory effect on bacterial growth, causing dental caries, periodontitis, dental plaque, and gingivitis. A study found that during experimental oral candidiasis, mice are protected by terpin-4-ol, which is one of the main chemical constituents present in Melaleuca alternifolia essential oil [134]. Melaleuca alternifolia Cheel is used in Australian traditional medicine.…”
Section: Melaleuca Alternifolia (Maiden and Betche) Cheelmentioning
confidence: 99%
“…Recently, in vivo trials conducted on melaleuca gel were reported to have an inhibitory effect on bacterial growth, causing dental caries, periodontitis, dental plaque, and gingivitis. A study found that during experimental oral candidiasis, mice are protected by terpin-4-ol, which is one of the main chemical constituents present in Melaleuca alternifolia essential oil [134]. Melaleuca alternifolia Cheel is used in Australian traditional medicine.…”
Section: Melaleuca Alternifolia (Maiden and Betche) Cheelmentioning
confidence: 99%
“…Furthermore [ 64 ], Donoyama and Ichiman (2006) reported that niaouli oil has antibacterial effects on Staphylococcus aureus . Niaouli essential oil was effective against pathogenic microorganisms resistant to antibiotics on the skin surface, and the effectiveness of P. aeruginosa on biofilm formation was determined by [ 65 , 66 ]. In another study, Ozdemir et al (2018) found that niaouli had strong antibacterial resistance of 13.0 ± 1.00 mm, 20.0 ± 1.00 mm, 21.0 ± 1.00 mm, 15.0 ± 1.00 mm, 17.0 ± 1.00 mm, 15.0 ± 1.00 mm, 35.0 ± 0.57 mm, and 13.0 ± 1.00 mm against Pseudomonas aeruginosa , Staphylococcus aureus , Escherichia coli , Enterococcus faecalis , Bacillus subtilis , Salmonella typhimurium , Staphylococcus epidermidis , and Enterococcus hirae , respectively [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The compounds α‐terpineol, germacrene‐D, ledene, α‐pinene, terpinolene, ρ‐cymene, β‐caryophyllene, limonene, and sabinene follow in lower concentrations. Both species are endemic to Australia, with M. alternifolia essential oil being used by traditional medicine topically due to its antimicrobial and antifungal potentials 27 . It is not the intention of this study to describe the composition of the essential oil of these species, instead these samples were selected by their easy access from commercial sources.…”
Section: Resultsmentioning
confidence: 99%